2009
DOI: 10.1681/asn.2008080843
|View full text |Cite
|
Sign up to set email alerts
|

IRF-1 Promotes Inflammation Early after Ischemic Acute Kidney Injury

Abstract: Acute renal ischemia elicits an inflammatory response that may exacerbate acute kidney injury, but the regulation of the initial signals that recruit leukocytes is not well understood. Here, we found that IFN regulatory factor 1 (IRF-1) was a critical, early proinflammatory signal released during ischemic injury in vitro and in vivo. Within 15 min of reperfusion, proximal tubular cells of the S3 segment produced IRF-1, which is a transcription factor that activates proinflammatory genes. Transgenic knockout of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 64 publications
(86 reference statements)
7
42
0
Order By: Relevance
“…3) We previously reported increased expression of IRF1 by renal tubule cells exposed to ROS in vitro (56). We now confirm and extend this result by showing ROS also stimulated expression of IFN␣s (Fig.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…3) We previously reported increased expression of IRF1 by renal tubule cells exposed to ROS in vitro (56). We now confirm and extend this result by showing ROS also stimulated expression of IFN␣s (Fig.…”
Section: Discussionsupporting
confidence: 85%
“…We previously showed that ROS generated during ischemia (34,35,58) increases the expression of IRF1 in proximal tubule cells in vitro (56). We now find that IFN␣ mRNA is significantly increased in tubule cells following exposure to ROS in vitro, and this increase is prevented by IRF1 knockdown (Fig.…”
Section: Irf1 Regulates the Ros-driven Ifn␣ Expression By Renal Tubulsupporting
confidence: 52%
See 1 more Smart Citation
“…IRF4 was found to be induced not before 24 h after ROS exposure in spleen monocytes, which was consistent with increased renal IRF4 expression 24 h after renal artery clamping, a phenomenon entirely prevented by antioxidant treatment. As such, oxidative stress does not induce IRF4 as an early response gene like IRF1, which was previously shown to respond within 15 min of oxidative stress (41). The delayed IRF4 response versus the rapid induction of IRF1 is interesting because IRF-1 promotes postischemic renal inflammation and acute renal failure (41), whereas our data documents the opposite for IRF4.…”
Section: Discussionsupporting
confidence: 46%
“…Our data document that oxidative stress adds onto the list of triggers for IRF4 induction, which suggests IRF4 regulates the activation of resident APCs in ischemic tissues. This was evidenced by exposing monocytes to hypoxanthine and xanthineoxidase, which generate ROS and induce stress response genes like HSP70 in a controlable manner in vitro (41). IRF4 was found to be induced not before 24 h after ROS exposure in spleen monocytes, which was consistent with increased renal IRF4 expression 24 h after renal artery clamping, a phenomenon entirely prevented by antioxidant treatment.…”
Section: Discussionmentioning
confidence: 71%